Hubungan antara Kecerdasan Buatan (Artificial Intelligence) dengan Manusia menurut Pandangan Magisterium Katolik - Tumanggor, Felicitas Adelita Permatasari; Christianto, Gabriel Enrico; Prasetio, Viana Meilani; Tumanggor, Raja Oloan (Innovative: Journal Of Social Science Research, 2025)
Various aspects of human life, including the way people think, act, and interact with one another, have been affected by advances in artificial intelligence (AI) technology. Amidst these advances, profound theological and ethical questions arise about how technology affects human dignity, moral freedom, and their relationship with God and fellow human beings. Through the document Antiqua et Nova, issued on January 28, 2025, by the Dicastery for the Doctrine of the Faith, the Catholic Church provides a clear and profound response to these dynamics. The document states that technologies such as AI should not replace the moral role of humans. Rather, they should be used to enhance the dignity of the human person and the common good as the image of God. In this situation, the purpose of this paper is to examine the relationship between artificial intelligence and human values from the perspective of the Catholic Church. Views on moral values, the principle of prudence, and moral responsibility for technological progress are some of the main themes in Antiqua et Nova. This study concludes through a reflective-theological and qualitative approach that technological progress can only be beneficial if it is used for the service of humanity and not vice versa. Thus, this study is expected to contribute to building moral and spiritual awareness in facing the digital era and artificial intelligence.